Refractive Error Development in Children with Intermittent Exotropia - F Senobari; M Etezad Razavi; M Najjaran; H Ostadimoghaddam; E Bakhtiari (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Intermittent exotropia is the most common type of outward deviation of the eye in childhood. The association between myopia refractive error and intermittent exotropia has been shown in very few studies. This study was conducted to investigate the association between various refractive errors and the course of their changes in patients with intermittent exotropia. Methods: This retrospective study was conducted on 130 patients with intermittent exotropia younger than 16 years of age who referred to Khatam-al-Anbia Eye Hospital in Mashhad. The records of patients with follow-up were reviewed in terms of age, gender, and near and distance angles of deviation using cover test, type and grade of refractive errors at the initial visit and subsequent visits using cycloplegic drops, types of treatments performed, and dominance of the patients' eyes. Changes in refractive errors during different visits in the patients were examined and compared. Findings: The mean age of the patients was 5.64±4.08 years, of which 77 (59.2%) were girls. The mean distance deviation angle of the patients was 30.79±12.13 prism diopters and the mean near deviation angle was 24.27±17.85 prism diopters. The most common treatment performed for the patients was patch therapy (57.4%). At the initial visit, 77 patients (54%) were hyperopic. In the non-dominant eye, changes in refractive errors towards a decrease in spherical refraction were significant (p=0.002). Conclusion: The results of this study showed that most patients were hyperopic and the course of changes was towards a decrease in spherical equivalent (shift towards myopia).